Relationship between acne vulgaris and attention-deficit/hyperactivity disorder symptoms in a clinical sample of women - Ayhan Bilgic; Özlem Bilgic; Rukiye Sivri Çolak; Hilmi Cevdet Altınyazar (Sociedade Brasileira de Dermatologia, 2016)
Abstract Acne vulgaris has recently been reported to be associated with elevated rates of attention deficit/hyperactivity disorder in epidemiological studies. This report examines childhood and current attention-deficit/hyperactivity disorder symptoms in a clinical sample of female adults. Ninety-one women with acne vulgaris and 53 controls were included in this study. The aforementioned symptoms were measured in participants. No significant differences were found between patients and controls in any of the measurements. Contrary to the findings of epidemiological studies, this study did not uncover a link between acne vulgaris and attention-deficit/hyperactivity disorder